Does Competency-Based Education Have a Role in Academic Pharmacy in the United States? - Melissa S. Medina (MDPI AG, 2017)
Competency-based Education (CBE) is an educational model that allows students to learn and demonstrate their abilities at their own pace. CBE is growing in popularity in undergraduate educational programs and its role in pharmacy education in the United States (US) is under review. In comparison, medical education is utilizing competency-based approaches (such as competencies and Entrustable Professional Activities) to ensure that students possess the required knowledge, skills, and attitudes prior to graduation or program completion. The concept of competency-based approaches is growing in use in pharmacy education in the US, but the future related to aspects of this concept (e.g., mandatory Entrustable Professional Activities) is not certain. A review of pharmacy education's evolution in the US and a comparison of competency-related terms offers insight into the future use of competency-based approaches and CBE in pharmacy education in the US through the lens of benefits and challenges.